Rancang Bangun Pot Pintar Berbasis IoT - Artdhita Fajar Pratiwi; Galih Mustiko Aji; Arif Sumardiono; Purwiyanto; Sari Widya Utami (J-Innovation, 2022)
This study aims to create a smart pot that can automatically maintain indoor ornamental plants. This research begins with designing a pot model in a 3-dimensional image and fabricating using a 3D printer. The pot consists of 3 parts, namely the lower part for storage of the controller, the middle part as a place for nutrient water, and the upper part as a planting medium. Smart pots are equipped with sensors to support plant growth such as temperature and humidity sensors, soil moisture sensors, and water level sensors for plant nutritional needs. This system can be monitored and controlled remotely using an android smartphone if it is connected to Wi-Fi. The android application is made using MIT App Inventor which is connected to the firebase database so that it can be monitored via the internet remotely. Sensor data is sent in real-time and stored in the firebase database in the cloud. The test results show that the sensors in the pot are able to respond in real-time during the process of maintaining ornamental plants. The android application created can display indicators and the status of the plant microenvironment in more detail than the display on hardware.